Idiopathic Paroxysmal Tonic Upward Gaze - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
A case of paroxysmal tonic upward gaze with neck flexion in a 14-month-old boy is reported from a Department of Neurology in Izmir, Turkey.